Three‐dimensional rotational angiography in congenital heart disease: Present status and evolving future. (4th September 2019) - Kang, Sok‐Leng; Armstrong, Aimee; Krings, Gregor; Benson, Lee
Abstract: Three‐dimensional rotational angiography (3D‐RA) enables volumetric imaging through rotation of the C‐arm of an angiographic system and real‐time 3D reconstruction during cardiac catheterization procedures. In the field of congenital heart disease (CHD), 3D‐RA has gained considerable traction, owing to its capability for enhanced visualization of spatial relationships in complex cardiac morphologies and real time image guidance in an intricate interventional environment. This review provides an overview of the current applications, strengths, and limitations of 3D‐RA acquisition in the management of CHD and potential future directions. In addition, issues of dosimetry, radiation exposure, and optimization strategies will be reviewed. Further implementation of 3D‐RA will be driven by patient benefits relative to existing 3D imaging capabilities and fusion techniques balanced against radiation exposure.